1995
DOI: 10.1111/j.1365-2958.1995.tb02339.x
|View full text |Cite
|
Sign up to set email alerts
|

The global regulatory protein FruR modulates the direction of carbon flow in Escherichia coli

Abstract: The Escherichia coli fructose repressor, FruR, is known to regulate expression of several genes concerned with carbon utilization. Using a previously derived consensus sequence for FruR binding, additional potential operators were identified and tested for FruR binding in DNA band migration retardation assays. Operators in the control regions of operons concerned with carbon metabolism bound FruR, while those in operons not concerned with carbon metabolism did not. In vivo assays with transcriptional lacZ fusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
159
2
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(168 citation statements)
references
References 38 publications
6
159
2
1
Order By: Relevance
“…1). In a fruR deletion mutant, therefore, a faster carbon flow from glucose results (Ow et al, 2007;Ramseier et al, 1995). Consequently, there is a more rapid availability of formate when cells are fermenting glucose and this was reflected in a 40 % increase in total hydrogenase activity observed at the 6 h time point in the fruR mutant CP462 (Table 2).…”
Section: Growth Of Mc4100 On Fructose Reduces Total Measurable Hydrogmentioning
confidence: 90%
See 1 more Smart Citation
“…1). In a fruR deletion mutant, therefore, a faster carbon flow from glucose results (Ow et al, 2007;Ramseier et al, 1995). Consequently, there is a more rapid availability of formate when cells are fermenting glucose and this was reflected in a 40 % increase in total hydrogenase activity observed at the 6 h time point in the fruR mutant CP462 (Table 2).…”
Section: Growth Of Mc4100 On Fructose Reduces Total Measurable Hydrogmentioning
confidence: 90%
“…FruR-dependent repression of fruBKA operon expression, and consequently regulation of fructose utilization, can be counteracted by increased concentrations of fructose-1-phosphate and fructose-1,6-bisphosphate (Saier & Ramseier, 1996). Thus, increased fructose-1-phosphate concentrations in a fruK mutant reverse the FruR-mediated metabolic flux increase (Ramseier et al, 1995). Introduction of the fruK allele from JW2155 (see Table 1 for genotype), generating strain CP461, restored an intact copy of the fruB gene on the chromosome of MC4100; however, analysis of CP461 (DfruK) revealed that growth was still poor in the presence of fructose (Fig.…”
Section: Growth Of Mc4100 On Fructose Reduces Total Measurable Hydrogmentioning
confidence: 99%
“…Several previous studies have reported the results of searches for binding sites of particular proteins in E. coli, including LexA (Lewis et al, 1994), FruR (Ramseier et al, 1995), Fis (Verbeek et al, 1990), and Lrp (Cui et al, 1995). We have created a library of 61 search matrices for 55 different E. coli DNA-binding proteins.…”
Section: E Coli Matrix Searchesmentioning
confidence: 99%
“…Escherichia coli contains at least 240 proteins that are known or predicted to be DNA-binding proteins (Robison, 1997). Known binding sites for a DNA-binding protein can be used to identify additional sites for that protein, and thereby identify further genes regulated by that protein (Wasserman & Fickett, 1998;Tronche et al, 1997;Fondrat & Kalogeropoulos, 1996;Goodrich et al, 1990;Lewis et al, 1994;Ramseier et al, 1995;Stormo, 1990;Verbeek et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Catabolite Repression of PEP Carboxykinase and the Glyoxylate Shunt-To verify the in vivo evidence for the unexpected anaplerotic switch, we determined in vitro activities of the catabolite-repressed PEP carboxykinase and isocitrate lyase (6,26,28) and of the normal glucose metabolism enzymes PEP carboxylase and isocitrate dehydrogenase (Table II). Consistent with previous reports (12,25), the more rapidly growing chemostat cultures at growth rates of 0.2 and 0.4 h Ϫ1 were similar to batch cultures, as would be expected from increased catabolite repression under these conditions (9 -11).…”
Section: The Pep-glyoxylate Cycle In Escherichia Colimentioning
confidence: 99%